2014
DOI: 10.1002/jssc.201301291
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plant growth regulators in pears by microwave‐assisted extraction and liquid chromatography with electrospray ionization mass spectrometry

Abstract: A new method for the determination of six plant growth regulators, 3-indolylacetic acid, 3-indolepropionic acid, 2-naphthoxyacetic acid, 2,4-dicholrophenoxyacetic acid, 1-naphthlcetic acid, and methyl naphthalene-1-acetate, in pears was established by liquid chromatography with electrospray ionization mass spectrometry. In this study, a microwave-assisted extraction technique was first applied for the determination of plant growth regulators in fruit and three cleanup techniques were, respectively, investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…They stimulate cell division and promote cell elongation (Katzy et al, 1990;Weyers & Paterson, 2001). They are abundant in higher plants and rhizospheric microorganisms and play a vital role in plant-microbe interactions (Beneduzi et al, 2008;Costacurta & Vanderleyden, 1995;Lambrecht et al, 2000;Beck, Hansen & Lauritsen, 2003;Mao et al, 2014). Previous studies have demonstrated that Paenibacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…They stimulate cell division and promote cell elongation (Katzy et al, 1990;Weyers & Paterson, 2001). They are abundant in higher plants and rhizospheric microorganisms and play a vital role in plant-microbe interactions (Beneduzi et al, 2008;Costacurta & Vanderleyden, 1995;Lambrecht et al, 2000;Beck, Hansen & Lauritsen, 2003;Mao et al, 2014). Previous studies have demonstrated that Paenibacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are interferences in fruit extract such as sugars, organic acids, pigment, and some other coextractives. So the complex sample matrix would contribute to interferences or high background noise in detection of PGRs . Therefore, it is necessary to further develop appropriate enrichment and cleanup steps before the analysis to obtain accurate analytical data.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC–MS/MS operated in multiple reaction monitoring mode is the most commonly used technique for the highly sensitive and selective analysis of phytohormones. However, it has been mainly confined to several phytohormones from species of fruits , rice , and oilseed .…”
Section: Introductionmentioning
confidence: 99%